CUTANEOUS MANIFESTATIONS OF MIGRAINE: FIRST OF ITS KIND, TWO CASE REPORTS FROM PAKISTAN - Muhammad, Anjum; Iftikhar, Nadia; Iftikhar, Ahsan; Sarwar Abbasi, Ammar (Journal of Ayub Medical College Abbottabad, 2024)
Migraine is a common clinical entity; however, its dermatological manifestations are rarely reported. We report two young Pakistani female patients with asymptomatic, linear and round erythematous non blanchable patches on their forehead that were temporally associated with their migraine attacks. The local and systemic examination as well as extensive investigations, of both the patients, were all normal. The lesion resolved within a few days following abortion of migraine attacks in these patients. With Pathophysiology of cutaneous manifestations of migraine is still unknown due to their rare presentation, research is required to establish their significance in the long-term outcome of migraine.